Experience with virtual planning and stereolithographic models in plastic surgery - Gaviria-Pinzon, Jorge; Ruiz, Giancarlo; Garcia, Maria Paula; Gutierrez, Carlos David; Bermudez, Luis Eduardo (International Surgery Journal, 2022)
The use of stereolithographic models and virtual planning in plastic surgery have been used mainly in craniomaxillofacial reconstructions secondary to trauma, oncological reconstructions, orthognathic surgery and correction of craniofacial developmental anomalies of craniofacial development, among others, making surgical planning a less tedious process and reducing surgical time. In this article we present the experience using this technology in a referral center. Eight cases are exposed where the different applications of virtual planning and 3D models can be evidenced. Pre-op and post-op images are presented showing the similarity with the planning. We have implemented its use not only for facial trauma reconstructions with free flaps, but also for the correction of sequelae, correction of complex craniofacial abnormalities, oncological defects, and hand reconstructions. Our experience has been favorable since it allowed us to obtain satisfactory functional and predictable results and a reduced surgical time, especially in complex cases. If available, this technology should be considered as a useful tool to obtain predictable and reliable results.